Towards Photothermal Acid Catalysts Using Eco-Sustainable Sulfonated Carbon Nanoparticles—Part I: Synthesis, Characterization and Catalytic Activity towards Fischer Esterification - Militello, María Paula (2023)
The development of photothermal catalysts for biodiesel synthesis reaction (transesterification) requires the production of light-absorbing nanoparticles functionalized with catalytic (acid) groups. Using Stöber method, it is possible to produce resorcinol/formaldehyde resin (RF) nanoparticles, which can be carbonized (pyrolysis in an inert atmosphere) and sulfonated. In this work, vegetable tannins are used as a replacement for synthetic resorcinol in the Stöber synthesis of resin (TF) nanoparticles. The nanoparticles are characterized using DLS, FESEM, TEM and N2 adsorption-desorption isotherms. Both resin and carbon nanoparticles are sulfonated by reaction with concentrated sulfuric acid. The attachment of sulfonic groups is verified by FTIR and EDX. The number of sulfonic groups is measured by acid/base titration and TGA. All sulfonated nanoparticles show catalytic activities towards Fischer esterification of ethanoic acid with ethanol, and high (up to 70%) conversion is obtained. The conversion is lower with TF-based nanoparticles, but the turnover numbers are similar in the RF- and TF-based materials. Sulfonated carbon and resin nanoparticles show higher catalytic activity compared to commercial acidic catalysts (e.g., Nafion®). Photothermal heating of carbon nanoparticles is observed. In Part II, sunflower oil transesterification, catalyzed by sulfonated nanoparticles, is observed. Photothermal catalysis of acetic acid esterification and sunflower oil transesterification is demonstrated.